Expression and transport activity of breast cancer resistance protein (Bcrp/Abcg2) in dually perfused rat placenta and HRP-1 cell line - Staud, Frantisek; Vackova, Zuzana; Pospechova, Katerina; Pavek, Petr; Ceckova, Martina; Libra, Antonin; Cygalova, Lenka; Nachtigal, Petr; Fendrich, Zdenek (The Journal of pharmacology and experimental therapeutics, 2006)
Breast cancer resistance protein (BCRP/ABCG2) is a member of the ATP-binding cassette transporter family that recognizes a variety of chemically unrelated compounds. Its expression has been revealed in many mammal tissues, including placenta. The purpose of this study was to describe its role in transplacental pharmacokinetics using rat placental HRP-1 cell line and dually perfused rat placenta. In HRP-1 cells, expression of Bcrp, but not P-glycoprotein, was revealed at mRNA and protein levels. Cell accumulation studies confirmed Bcrp-dependent uptake of BODIPY FL prazosin. In the placental perfusion studies, a pharmacokinetic model was applied to distinguish between passive and Bcrp-mediated transplacental passage of cimetidine as a model substrate. Bcrp was shown to act in a concentration-dependent manner and to hinder maternal-to-fetal transport of the drug. Fetal-to-maternal clearance of cimetidine was found to be 25 times higher than that in the opposite direction; this asymmetry was partly eliminated by BCRP inhibitors fumitremorgin C (2 microM) or N-(4-[2-(1,2,3,4-tetrahydro-6,7-dimethoxy-2-isoquinolinyl)ethyl]-phenyl)-9,10-dihydro-5-methoxy-9-oxo-4-acridine carboxamide (GF120918; 2 microM) and abolished at high cimetidine concentrations (1000 microM). When fetal perfusate was recirculated, Bcrp was found to actively remove cimetidine from the fetal compartment to the maternal compartment even against a concentration gradient and to establish a 2-fold maternal-to-fetal concentration ratio. Based on our results, we propose a two-level defensive role of Bcrp in the rat placenta in which the transporter 1) reduces passage of its substrates from mother to fetus but also 2) removes the drug already present in the fetal circulation.
Keywords: buněčné linie; ATP-Binding Cassette Transporters; Metabolic Clearance Rate; Rats; placenta; Immunohistochemistry; cimetidin; potkani Wistar; Animals; metabolická clearance; Perfusion; perfuze; zvířata; ATP Binding Cassette Transporter, Subfamily G, Member 2; ABC transportér z rodiny G, člen 2; krysa rodu Rattus; ABC transportéry; imunohistochemie; messenger RNA; Rats, Wistar; ženské pohlaví; ATP Binding Cassette Transporter, Subfamily B, Member 1; Female; Placenta; Cell Line; Cimetidine; P-glykoprotein; RNA, Messenger